Tinjauan Yuridis terhadap Penyelesaian Sengketa Waris melalui Akta Perdamaian di Pengadilan Negeri Jakarta Pusat berdasarkan Putusan Nomor 582 Pdt G 2025 PN Jkt Pst - Rayi Kharisma Rajib; Citra Bethari Ratih; Nayla Oktri Ramadhani (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study aims to juridically analyze the settlement of inheritance disputes through a deed of settlement at the Central Jakarta District Court based on Decision Number 582/Pdt.G/2025/PN Jkt.Pst. Inheritance disputes are one of the civil disputes that frequently occur, particularly regarding the distribution of inheritance assets. In this case, the parties chose mediation, which was then formalized in a deed of settlement that is final and legally binding. This research employs a normative juridical approach using statutory and case study methods. The findings indicate that dispute resolution through a deed of settlement provides legal certainty, procedural efficiency, and upholds the principle of family consensus. Based on the decision, the parties agreed to divide the inheritance object in the form of land and buildings equally, with executorial force equivalent to a final and binding court judgment. The legal basis includes Article 130 HIR, Article 1338 of the Civil Code, and Article 27 paragraph (4) of Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court.